Respuesta :

bcalle
let the first integer be x
adding one to x (to represent the next integer) you get x + 1
adding two to x to get the next integer you get x + 2
the expression that represents three consecutive integers is x + (x + 1) + (x + 2)
Now we need to set this equal to 75 and solve.
x + (x + 1) + (x + 2) = 75
3x + 3 = 75
subtract 3 from both sides
3x + 3 - 3 = 75 - 3
3x = 72
to clear the multiplication by 3, divide both sides by 3
3x/3 = 72/3
x = 24
x + 1 = 25
x + 2 = 26
24, 25, 26 are the three integers
ACCESS MORE